Factors Influencing The Implementation Of Pregnant Women's Exercise In The Work Area Of Medan Johor Health Center, Medan City, Medan City In 2024 - Lenny Sepriani Br Silalahi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pregnancy exercise is an effort to improve the health of mothers and babies during pregnancy. Maternal participation in pregnancy exercise in Indonesia is still low, including in Medan City, of 168 pregnant women, 140 of them did not take part in pregnancy exercise. Survey results at the Medan Johor Community Health Center showed that pregnant women did not participate in pregnancy exercise due to lack of knowledge and lack of motivation (60%). The aim of this research is to identify factors that influence the implementation of pregnancy exercise in the Medan Johor Community Health Center Work Area, Medan City in 2024. This type of research is an analytical survey using an approach cross-sectional. The population of this study was all 135 pregnant women aged 22 weeks and over. The sampling technique uses the method proportional samplingas many as 101 people. Data analysis uses univariate and bivariate analysis with tests chi square and multivariate with logistic regression. The results of research using logistic regression are known valuesp-value Logistic regression of educational variables 0.808>0.05, knowledge 0.021<0.05, family support 0.000<0.05 and motivation 0.000<0.05. It is recommended that pregnant women actively participate in outreach programs to increase their knowledge and carry out pregnancy checks and participate in pregnancy exercises.